2019
DOI: 10.1523/jneurosci.1163-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Beta Oscillations in Working Memory, Executive Control of Movement and Thought, and Sensorimotor Function

Abstract: Beta oscillations (ϳ13 to 30 Hz) have been observed during many perceptual, cognitive, and motor processes in a plethora of brain recording studies. Although the function of beta oscillations (hereafter "beta" for short) is unlikely to be explained by any single monolithic description, we here discuss several convergent findings. In prefrontal cortex (PFC), increased beta appears at the end of a trial when working memory information needs to be erased. A similar "clear-out" function might apply during the stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
221
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(236 citation statements)
references
References 98 publications
14
221
0
1
Order By: Relevance
“…Alpha/beta and gamma rhythms are common and anti-correlated across the cortex but it has been unclear whether or not they have similar functional relationship in different areas. Frontal beta rhythms have been associated with top-down attention, inhibiting motor actions, and working memory storage (Schmidt et al, 2019: Lundqvist et al, 2016Buschman and Miller, 2007). Occipital and parietal alpha has been linked to inhibition of unattended stimuli (Klimesch et al, 1998;Jokisch and Jensen, 2007;van Ede et al, 2011;Bollimunta et al, 2011;Rohenkohl and Nobre, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alpha/beta and gamma rhythms are common and anti-correlated across the cortex but it has been unclear whether or not they have similar functional relationship in different areas. Frontal beta rhythms have been associated with top-down attention, inhibiting motor actions, and working memory storage (Schmidt et al, 2019: Lundqvist et al, 2016Buschman and Miller, 2007). Occipital and parietal alpha has been linked to inhibition of unattended stimuli (Klimesch et al, 1998;Jokisch and Jensen, 2007;van Ede et al, 2011;Bollimunta et al, 2011;Rohenkohl and Nobre, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Occipital and parietal alpha has been linked to inhibition of unattended stimuli (Klimesch et al, 1998;Jokisch and Jensen, 2007;van Ede et al, 2011;Bollimunta et al, 2011;Rohenkohl and Nobre, 2011). Gamma power increases (and alpha/beta power decreases) in sensory cortex during sensory input and before/during movements in motor cortex (Brovelli et al, 2004;Cheyne et al, 2008;Schmidt et al, 2019;Fries et al, 2001, Gray et al, 1990Gevins et al, 1997;Fisch et al, 2009). Frontal beta, and premotor alpha are correlated with reduced spike rates (Haegens et al, 2011;Lundqvist et al, 2016;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other neural recording data, it is difficult to determine what the observed 20-40 Hz power dynamics reflect in terms of information processing and how they are linked with behavior. Oscillations in this range (typically referred to as beta) occur widely across the cortex and have been associated with different functions across brain regions (Engel & Fries, 2010; Schmidt et al, 2019). Of particular relevance here, beta has been associated with olfactory processing (Martin & Ravel, 2014), temporal estimation (Wiener, Parikh, Krakow & Coslett, 2018), working memory (Miller, Lundqvist & Bastos, 2018), and postural maintenance (Kilavik et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mapelli & Özkurt (2019) showed that alpha-beta activity in the parieto-occipital cortex was larger in incorrectly-than correctly-answered trials of a vWM task. The enhanced alpha/beta powers in a retention period (Jensen et al, 2002;Palva et al, 2011) therefore might reflect the decay or "clearing-out" (not maintenance) of WM contents Schmidt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%